Detrimental Effects of Paraquat on Astrocytes-Regulating Synaptic Functions - Zheng Li; Jing Zheng; Xiao-Feng Zhang (SAGE Publishing, 2018)
Paraquat (PQ) exposure is known as a risk factor for developing neurodegenerative diseases. Astrocytes are implicated and affected in neurodegenerative diseases and brain injuries, so it is suspected that PQ may impose detrimental effects on astrocytes function. Here, we present a study of the effects of PQ on synaptic function of astrocytes. Human astrocytes (HA1800) were separately treated with PQ at 200, 400, and 800 µmol/L for 12, 24, and 48 hours, respectively. The concentrations of membrane cholesterol, intracellular glutamate, and adenosine triphosphate (ATP) were assessed by measuring changes with Kits after PQ treatment. Expression levels of glial fibrillary acidic protein (GFAP) and apolipoprotein E (ApoE) were detected using Western blot method. The results indicated that astrocytes were highly susceptible to PQ showing astrogliosis characterized by enhanced GFAP expression ( P < .05). The decreased cholesterol level and ApoE expression were observed in PQ-treated astrocytes and so were the decreased levels of glutamates and ATP in PQ-treated astrocytes. These results suggested that PQ exerted the detrimental effects on synaptic function of astrocytes, which may be involved in the progressive process of neurodegenerative disorders.